Developing guidelines in low-income and middle-income countries: lessons from Kenya. Issue 9 (5th June 2017) - English, Mike; Irimu, Grace; Nyamai, Rachel; Were, Fred; Garner, Paul; Opiyo, Newton
Abstract : There are few examples of sustained nationally organised, evidence-informed clinical guidelines development processes in Sub-Saharan Africa. We describe the evolution of efforts from 2005 to 2015 to support evidence-informed decision making to guide admission hospital care practices in Kenya. The approach to conduct reviews, present evidence, and structure and promote transparency of consensus-based procedures for making recommendations improved over four distinct rounds of policy making. Efforts to engage important voices extended from government and academia initially to include multiple professional associations, regulators and practitioners. More than 100 people have been engaged in the decision-making process; an increasing number outside the research team has contributed to the conduct of systematic reviews, and 31 clinical policy recommendations has been developed. Recommendations were incorporated into clinical guideline booklets that have been widely disseminated with a popular knowledge and skills training course. Both helped translate evidence into practice. We contend that these efforts have helped improve the use of evidence to inform policy. The systematic reviews, Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approaches and evidence to decision-making process are well understood by clinicians, and the process has helped create a broad community engaged in evidence translation together with a social or professional norm to use evidence in paediatric care in Kenya. Specific sustained efforts should be made to support capacity and evidence-based decision making in other African settings and clinical disciplines.